Patočka and Rorty – The Problem of Freedom - Mayerová, Katarína (Folia Philosophica, 2016)
Patočka´s and Rorty´s philosophy offer a foundation for the reconstruction of liberalism and a possibility of fulfilling individual´s freedom. Patočka intends to assess the value of transcendence and its relevance to life. He tries to save the metaphysics for it does not need to become necessarily dogmatic. Contemporary people may find Patočka´s reflections on freedom beneficial. Patočka invites people to connect their spirituality with skepticism and modesty, and according to Socratic knowing of unknowing, along with humility which makes man non-dogmatically open to transcendence. In the reflections on man, Rorty holds to moral responsibility and tries to bring man to self-awareness and taking responsibility for his acting, because it is only man who disposes of unique possibilities and abilities to shape his own authentic way of life. Rorty´s concept of freedom as an accidental phenomenon is based on the concept of history of Western philosophy and is closely linked with the problem of metaphysics and truth. Despite timeless reflections of both philosophers, any timeless ideal of human freedom is determined by the context in which we are thinking.